1992
DOI: 10.1055/s-0038-1648397
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Isolation of Human Endothelial Cells from Whole Blood Using S-Endo1 Monoclonal Antibody Coupled to Immuno-Magnetic Beads: Demonstration of Endothelial Injury after Angioplasty

Abstract: SummaryThe presence in whole blood of circulating endothelial cells (EC) has been a subject of debate for many years. It could represent a good marker of vessel injury. We demonstrate here that human endothelial cells can be directly isolated and identified in circulating blood by means of an endothelial cell specific monoclonal antibody, S-Endol, coupled to micromagnetic beads. The specificity and efficacy of the assay were established using normal blood samples with cultured EC added. Specific rosettes forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0
3

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(87 citation statements)
references
References 24 publications
2
82
0
3
Order By: Relevance
“…However, the amount of CECs detectable in peripheral blood has been recently proposed as a reliable marker of endothelial damage in different vascular diseases, such as acute coronary syndrome (also after coronary angioplasty), sickle cell anemia, thrombotic thrombocytopenic purpura, rickettsial and cytomegalovirus infections, Behçet's disease, SLE, and small-vessel vasculitides (7)(8)(9)(10)(11)(12)(13)(14)(15). Thus, the detection of CECs in patients with SSc is certainly not surprising, because results of several histologic studies of dermal microvas- culature in this disease, which demonstrated disruption of the normal architecture of the endothelium with loss of intercellular junctions and progressive death of endothelial cells (3)(4)(5)(6), have suggested that endothelium may play a key role in the pathologic process of SSc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the amount of CECs detectable in peripheral blood has been recently proposed as a reliable marker of endothelial damage in different vascular diseases, such as acute coronary syndrome (also after coronary angioplasty), sickle cell anemia, thrombotic thrombocytopenic purpura, rickettsial and cytomegalovirus infections, Behçet's disease, SLE, and small-vessel vasculitides (7)(8)(9)(10)(11)(12)(13)(14)(15). Thus, the detection of CECs in patients with SSc is certainly not surprising, because results of several histologic studies of dermal microvas- culature in this disease, which demonstrated disruption of the normal architecture of the endothelium with loss of intercellular junctions and progressive death of endothelial cells (3)(4)(5)(6), have suggested that endothelium may play a key role in the pathologic process of SSc.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, CECs have been detected in diverse conditions having in common endothelial damage, such as coronary angioplasty, acute coronary syndrome, sickle cell anemia, thrombotic thrombocytopenic purpura, infection with Rickettsia conorii or cytomegalovirus, Behçet's disease, systemic lupus erythematosus (SLE), and small-vessel vasculitis (7)(8)(9)(10)(11)(12)(13)(14)(15). Moreover, it has been suggested that in response to severe ischemia or cytokine stimuli, circulating endothelial cell progenitors (CEPs) increase and home into sites of angiogenesis and/or vascular damage, and consequently contribute to neovascularization and/or wound-healing processes (16)(17)(18).…”
Section: Conclusion the Presence Of Cecs In Patientsmentioning
confidence: 99%
“…The most widely used method to isolate CEC, is by the use of magnetic beads coupled to a monoclonal antibody (mAb) targeting CD146, as first described by Dignat-George (George et al, 1992). After isolation, additional techniques, such as flow cytometry or microscopic analysis, are used to identify CEC based on morphological or immunophenotypical criteria.…”
Section: Available Assays Manual Immunomagnetic Isolationmentioning
confidence: 99%
“…Gaynor et al 5 measured the number of circulating endothelial cells (CECs) in the blood of rabbits administered a dose of endotoxin, and reported an increase in the CEC concentration, which suggested that CECs could serve as a marker to measure vascular injury. Indeed, CEC concentrations have been found to be altered in patients with a variety of vascular injury and disease, including coronary angioplasty, 6 acute coronary syndromes and unstable angina, 7 peripheral vascular disease, 8 and inflammatory vasculitis, 9 when conditioning for bone marrow transplantation, 10 and during organ transplant rejection. 11 More recently, CECs have been measured by CD146 expression, and changes in the concentration of CD146 þ cells have been used as a biomarker for many human disorders.…”
Section: Introduction and Initial Discovery Of Endothelial Progenitormentioning
confidence: 99%